Climate Change-Its Impact on Agriculture - Samoon3, G. I. Hassan4; Showket A. Dar5, Shabir Ahmad Wani1*, S. S. Mahdi2, S. A. (Journal of Phytology, 2011)
Global warming has effects and consequences on all walks of life. The consequences of global warming can be seen in the atmospheric weather, local climate change, glacier retreat and disappearance, oceans, seal level rise, acidification, forest fires, ozone depletion, agriculture, water scarcityÂ as well as the health of individuals. An increase of 2ÂºC in temperature could decrease the rice yield by about 0.75 t/ha and 0.5ÂºC increase in winter temperature reduce wheat yield 0.45 t/ha. Results showed that about 7.4, 8.7 and 9.8 per cent of total cumulative CO2, SO2 and NO2 emission respectively could be avoided between 1997 and 2015 by using efficient appliances. Improved training and general education of populations dependent on agriculture. Agriculture research to develop new crop varieties. Identification of the present vulnerabilities of agricultural systems. Food programmes and other social security programmes to provide insurance against supply changes. Transportation, distribution and market integration to provide the infrastructure to supply food during crop short falls. It is imperative that the developed countries and the rapidly developing countries formulate strategies to curb greenhouse gas emissions. Countries on the fast tract of economic growth should also look at adopting new energy-saving technologies and planting of more trees. The emphasis should also be laid on increasing the use of renewable energy sources like solar and wind. It is high time for leading emitters of CO2 to formulate national programmes to address climate change. Key words: Climatic change, Agriculture, Environment, Variables <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Shabir Ahmad Wani et al. Climate Change-Its Impact on Agriculture. J Phytol 2/10 (2010) 82-86